Tone perception and production in pediatric cochlear implants users. - Xu, Li; Chen, Xiuwu; Lu, Hongyun; Zhou, Ning; Wang, Shuo; Liu, Qiaoyun; Li, Yongxin; Zhao, Xiaoyan; Han, Demin (Acta Oto-Laryngologica, 2011)
Conclusions: In prelingually deaf children with cochlear implants, tone perception and production performance are highly correlated. This result is consistent with the hypothesis that tone perception is the prerequisite for good tone production. Objectives: Previous research has shown remarkable deficits in tone perception and production in native tone language-speaking, prelingually deafened children with cochlear implants. The purpose of the present study was to investigate the relationship between tone perception and production in those children. Methods: Twenty-five prelingually deaf children with cochlear implants participated in the study. All subjects were Advanced Bionics CII/90K users with various lengths of implant use. To evaluate tone perception performance, subjects completed a computerized tone contrast test. For tone production performance, an artificial neural network was used to evaluate the accuracy of tones recorded from each of the 25 subjects. Results: Large individual differences in tone perception and production performance were observed in these subjects. Tone perception accuracy ranged from 50.0 to 96.9% correct (chance performance == 50% correct; mean == 71.0% correct). Tone production performance ranged from 19.4 to 97.2% correct (mean == 52.0% correct). A strong correlation was found between tone perception and production performance in this group of subjects ( r == 0.805).